Alpine skiing injuries: ulnar collateral ligament sprains and tibia fractures - Bronder, Lucas; Savage, Maya; Sempala, Randi; Milligan, Anna-Marie (My University, 2020)
Skiing is an exciting winter sport; however, it is defined as a high-risk sport for significant injuries. Among upper body and lower body injuries, common traumas to the body in downhill skiers are sprains of the ulnar collateral ligament (UCL), which is part of the thumb joint, and tibia fractures. The analysis and research will outline the following of each injury: • Mechanism of injury • Treatment • Rehabilitation • Prevention.
A sport injury poster: alpine skiing
Keywords: skiing; sports injuries